TECHNOLOGICAL DESIGN OF CAR SERVICE STATIONS USING GENETIC ALGORITHMS - Nikolay S. Zakharov; Evgeniy S. Kozin (International Journal of Advanced Studies)
The study describes the use of evolutionary methods or genetic algorithms for the technological design of newly constructed or modernized car service stations. Genetic algorithms are one of the types of machine learning models and are actively used to solve multifactor optimization problems. A task of this type is to search for the technical parameters of a car service enterprise under which the economic indicators of its activities will correspond to the profit or capital cost restrictions set by the user. The paper presents the parameters of the developed model, fitness functions, and also provides an assessment of the effectiveness of using the method of genetic algorithms relative to the method of simply enumerating different options for combinations of initial factors.